Port Strategies for Robot-Assisted Lobectomy by High-Volume Thoracic Surgeons: A Nationwide Survey. Issue 6 (November 2019) - Oh, Daniel S.; Tisol, William B.; Cesnik, Larry; Crosby, Anna; Cerfolio, Robert J.
Abstract : Objective: Robot-assisted lobectomy is the fastest growing technique for pulmonary lobectomy, but the diversity of approaches has led to apprehension about port placement among learning surgeons. The aim of this study was to survey high-volume thoracic surgeons who perform robot-assisted lobectomy to understand and consolidate common themes of port placement. Methods: An electronic online survey was created, and the link was emailed to the 100 highest volume robotic thoracic surgeons in the United States. The survey included an interactive graphical interface, which allowed each respondent to mark the preferential robotic port placement in the chest wall for each of the 5 pulmonary lobectomies. Results were analyzed individually and in aggregate. A heat map was generated to show trends. Results: One hundred surgeons were surveyed (response rate: 62%). Most (90%) respondents utilized a 4-arm approach and 79% used a completely 4-arm portal approach with CO2 insufflation. Exact locations for each robotic port were reported by 60% of the surveyed surgeons and the results varied; however, most surgeons generally used the seventh to ninth interspaces for the camera and instruments. The use of multiple different interspace levels was common. Ninety-four percent of respondents used an additional nonrobotic assistant port. Conclusions: There is not a universal port strategy for robot-assisted lobectomy. However, placement of the camera and robotic ports low in the seventh to ninth interspaces is the most common approach. There are some nuances of stapling port strategies and sequence of port placement, which are identified.